Identification of Problems or Barriers in Medicine Procurement Process in Low- and Lower-Middle-Income Countries: A Narrative Review - Faradiba, Faradiba; Satibi, Satibi; Aditama, Hardika; Prasetyo, Septimawanto Dwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Medicine procurement at LLMIC is still a challenge because of low medicine availability. As far as we know, no studies have identified the problems in the procurement of medicine in LLMIC countries, and thus it becomes the objective of this narrative review. Articles were retrieved from PUBMED, Science Direct, Google Scholar, PLOS from May 14th, 2021 to May 22nd, 2021 with a number of key words. There are 89 articles identified by a keyword or abstract, including in Indonesian (n=23) and English (n=10). The main problems include the absence of drug formulary system and pharmacy and therapeutics committee in hospital (selection), inconsistencies in disease and prescribing patterns, improper method of calculating the needs (planning), insufficient medicine stock, and long lead time (procurement). Factors such as lack of pharmacists (human resources), lack of budget for procurement (organization), no supporting management information system, and tender failure by the pharmaceutical industry also hinder medicine procurement. Efforts to solve this problem should include multi sectors to strengthen the medical management and the supply chain.